Monitoring movement in MRI by measuring changes in the EMF induced in head-mounted coils - Bhuiyan, E. H. (2017)
Image quality is degraded by involuntary movement of the subject in an MRI scanner. It is fairly challenging in MRI of the brain to monitor the involuntary head movement accurately. Though there are a few techniques to monitor head movement of the subject for prospective motion correction, it is still an unsolved problem in MRI. In this study, head movement inside an MR scanner is monitored via measurement of changes in the voltage induced in head mounted coils by switched magnetic field gradients. The motion of a rigid body such as the human head is decomposed into two components: namely translation and rotation. There are three degrees of freedom (DOFs) for translational motion i.e. translation along the x, y and z axes and three rotational degrees of freedom for rotational motion i.e. rotation about the x, y and z axes. Head movement is monitored in a gradient field by measuring the change in induced voltage in head mounted coils. To calculate the change in induced voltage I follow two approaches: circular loops simulation, analytical as well as numerical calculations. I show that by using a standard method one can form a linear model to identify the position and orientation of the coils. An experimental arrangement is set up to check the validity of the analytical and numerical calculations. Experiments carried out with a rig of five coils verified that the changes in induced voltage in the coils is linear with respect to the changes in position of the coils. The linear model is also verified by comparing estimated positions obtained by using the coils to those found by image realignment of fast field echo (FFE) images using Statistical Parametric Mapping (SPM). We experimentally evaluate the new approach for monitoring head movement inside an MR scanner, which exploits the linear variation of the voltages induced in a set of coils by time-varying magnetic field gradients with respect to small changes in position/orientation. This approach was tested by attaching five coils to a structured agar phantom and a healthy volunteer's head. The results suggest that it is possible to estimate the position and orientation with 0.22 mm and 0.24˚ root-mean-square error using this set-up. The new approach could be used for prospective or retrospective motion correction. An experiment is also carried out by using free running EPI (Echo Planar Imaging) to track the head movement inside an MR scanner. There is a strong relation between head movement and EPI waveforms, the central point of the experiment is to track the head displacements via measuring induced voltage in the coils by using EPI waveforms during execution of free running EPI. The results obtained from the experiment reveal that the method is promising.